Factors Underlying Engagement in Facebook Support Groups of Female Infertility Patients. Issue 3 (June 2021) - Gazit, Tali; Amichai-Hamburger, Yair
Women dealing with infertility issues may well undergo a long process of treatments and they are also likely to feel empty, defective, inadequate and worthless. Some of these women join online support groups in order to share their experiences, get information and ease their pain. One important positive phenomenon of the Internet is the advent of online support groups. These are designed to foster well-being and increased social interaction, and to offer 24/7 availability with no geographical restrictions. This study, comprising 191 female participants who answered an online survey, focused on closed Facebook support groups, the members of which were women undergoing treatments for infertility. The study examined to what extent the degree of engagement by these women in online support groups could be predicted by external factors (family status, social and family support, the importance of the group and the duration of membership) and internal factors (extroversion, openness to experience, subjective happiness and loneliness). Findings show that higher levels of engagement in such Facebook support groups are predicted by the external factors, including having a child, longer duration of membership in the group, family support and the strongest predictor, perception of the group as important. Findings also show that higher levels of engagement in these groups are predicted by internal factors extroversion and openness to experience, as was found in previous studies of other populations. Results and future research are discussed.